DARATUMUMAB FOR THE TREATMENT OF MULTIPLE MYELOMA - Iversen, Katrine Fladeland; Plesner, Torben (Srpski medicinski časopis Lekarske komore, 2023)
Daratumumab is the first approved monoclonal antibody that targets the CD38 protein on the surface of myeloma cells. Historically, a well-established anti-myeloma protocol included oral melphalan and prednisolone as the standard of care. Apart from this, in a bit longer than two decades the high dose of melphalan followed by autologous stem cell transplantation became the standard for young and fit myeloma patients. Simultaneously, the prophylactic treatment of frequent and devastating skeletal complications was improved using intravenous bisphosphonate. In the following years, there came an era of significant improvements in anti-myeloma treatment that had an impact on survival rate of elderly and/or frail myeloma patients. The treatment included immunomodulatory drug thalidomide followed by the development of a less toxic and more effective analogue lenalidomide. At the same time, bortezomib, a first-in-class proteasome inhibitor, was introduced in the therapeutic protocols. Despite these improvements in survival, the prognosis remained poor for patients relapsing after treatment with bortezomib and lenalidomide with a median overall survival of only 9 months. After the initial dose escalation studies daratumumab resulted in a prolonged survival in the absence of significant killing of tumor cells through modulation of the immune system or the bone marrow microenvironment. The emerging picture showed that the addition of daratumumab alone or in combination improved the outcome in all myeloma patients without adding significantly to toxicity. Owing to this approach, myeloma patients live longer and have a better quality of life and there are further efforts to cure them which represents the main therapeutic goal.
Keywords: daratumumab; multiple myeloma; therapy; prognosis